Improving infectious adverse event reporting for children and adolescents enrolled in clinical trials for acute lymphoblastic leukemia: A report from the Children's Oncology Group. Issue 11 (9th September 2022) - Elgarten, Caitlin W.; Thompson, Joel C.; Angiolillo, Anne; Chen, Zhiguo; Conway, Susan; Devidas, Meenakshi; Gupta, Sumit; Kairalla, John A.; McNeer, Jennifer L.; O'Brien, Maureen M.; Rabin, Karen R.; Rau, Rachel E.; et al.
Abstract: Infections cause substantial morbidity for children with acute lymphoblastic leukemia (ALL). Therefore, accurate characterization of infectious adverse events (AEs) reported on clinical trials is imperative to defining, comparing, and managing safety and toxicity. Here, we describe key processes implemented to improve reporting of infectious AEs on two active phase III Children's Oncology Group (COG) ALL trials. Processes include: (a) identifying infections as a targeted toxicity, (b) incorporation of infection‐specific case report form questions, and (c) physician review of AEs with real‐time data cleaning. Preliminary assessment of these processes suggests improved reporting, as well as opportunities for further improvement.